E-Modul Membaca Teks Eksposisi Melalui SQ3R Menggunakan Aplikasi Android Untuk Siswa SMA - Dwi Pulsha Apriliande; Siti Samhati; Sumarti Sumarti (Universitas Lampung, 2020)
The limitation of teaching materials causes students need for more interesting teaching materials because the teacher always uses textbooks. This study aims to produce interactive multimedia teaching materials in the form of electronic modules (e-Module), describe eligibility, and test the effectiveness of e-Module reading exposition text through SQ3R. The DDD-E model research methods, that is decide, design, develop, and evaluate. Data collection techniques through interviews and questionnaires in three schools. The results showed 1) successfully developed interactive multimedia teaching materials in the form of “e-Module reading exposition text through SQ3R using an android application”, 2) the overall feasibility of e-Module was declared